ON A NEW SPECIES OF GENUS INDICOVALI PORA, SHINDE AND DESHMUKH, 1985 (CESTODA : DILEPIDIDAE) FROM VARANUS INDICUS - SANAP, N.P.; SHINDE, G.B.; BHAGWAN, H.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The present communication deals with a new species of the genus Indicovalipora Shinde and Deshmukh 1985 collected from Varanus indicus at Pathiri, Dist. Parbhani, M.S. India. It differ from all the known species of genus with characters, scolex oval, mature segment longer than broad, testes ! 16 in number, cirrus pouch medium, cirrus coiled, vagina wide, anterior to the cirrus pouch, ovary distinctly bilobed, Ootype is oval, genital pore Small, Vitellaria follicular, rounded,eggs Oval.